Comportamiento sísmico de pilas de puentes atirantados - Alcántar Sánchez, Juan Gerardo (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
This study aims at assessing the seismic behavior of piles of cable-stayed bridges for different deck-pile connections. A comparison of the response is performed for four different types of connections between the deck and the pile. The first type of connection consists in suspending the deck above the horizontal transverse beam that connects the two legs of the tower, in such a way that the deck is only supported by the cables of the bridge and by the fixed connection with the secondary piles. The second case is a fixed connection between the deck and pile, creating a monolithic connection between the two structural elements. The third case considers a seismic energy dissipation system (viscous devices), installed on the horizontal transverse beam is a connection between deck and pile through viscous dampers. Finally, a connection through lead rubber bearing base isolators located on the horizontal transverse beam and in some of the secondary piles. Seismic analyses were performed using seismic records of major earthquakes (mainly from the September 19, 1985, earthquake). A wide range of dominant periods was considered for the analyses of the bridge response. The prototype bridge is a cable-stayed bridge with two parallel cables in a fan arrangement. The total length of the main span is 520 m. Results from the study show that the nature of the earthquake can cause important changes in the behavior of the bridge, and the connection type, between the deck and the pile, drives to substantial changes on the displacement and forces demands on the pile.

Esta tesis se desarrolló con el objetivo de evaluar el comportamiento sísmico de pilas de puentes atirantados para distintas condiciones de vinculación con el tablero. Es decir, tratar de encontrar que tipo de conexión pila-tablero conduce a una mejor respuesta del puente y sus componentes. Las conexiones que se evaluaron fueron cuatro: la primera consiste en suspender el tablero por encima de los travesaños de las pilas principales es decir que el tablero es sólo sostenido por los tirantes del puente y las pilas secundarias; la segunda consiste en tener una conexión fija entre el tablero y la pila lo que se conseguiría con una conexión monolítica entre los dos elementos estructurales; la tercera consiste en una conexión por medio de amortiguadores viscosos, y por último, una conexión mediante aisladores de base fabricados de neopreno con un núcleo de plomo. Los análisis sísmicos se realizaron con registros sísmicos de sismos de gran magnitud (principalmente el sismo del 19 de septiembre de 1985). Se utilizaron acelerogramas que tuvieran sus respuestas máximas tanto en periodos cortos como en periodos largos. El modelo que se utilizó como base consta de un puente atirantado con dos planos de atirantamiento en abanico con una longitud del claro principal de 520m. Los resultados muestran que la naturaleza del sismo puede provocar grandes cambios en el comportamiento del puente y que el tipo de conexión entre el tablero y la pila puede modificar en gran medida la demanda sobre la pila tanto en elementos mecánicos como en desplazamientos.
Facultad de Ingeniería Civil. Maestría en Ingeniería en el Área de Estructuras
Keywords: info:eu-repo/classification/cti/7; FIC-M-2015-1408; Puente; Pilas; Desplazamientos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4066